27 - EFFECTS OF ELECTROMAGNETIC FIELDS EMITTED BY MATTRESS IN SCIATICA EXPERIMENTAL MODEL (Fiep Bulletin - online, 2011)
The sciatica can be regarded as a painful syndrome, in which pain is perceived at the end of the lower limb, and occur due compression of the sciatic nerve. Symptoms include pain and along the path of the nerve, sensory disturbances and muscular weakness. Extremely low electromagnetic fields are present in the environment and are used in health treatments. The aim of this study was to assess pain in animals undergoing an sciatica experimental model, and kept on mattresses with electromagnetic field. Twenty four Wistar rats were divided into three groups: G1 (n = 8) – sciatica and kept in plastic cage (control), G2 (n = 8) – sciatica and mattress without electromagnetic field, G3 (n = 8) – sciatica and mattress emitting electromagnetic field (2.5 mG). The sciatica was induced by sciatic nerve compression, near the belly of the biceps femoris. Pain assessment was performed by the Functional Disability Test, which assesses the paw elevation time (PET) of the animal walking on a metal cylinder, for 1 minute. The evaluations were performed: pre-sciatica, and 3, 4, and 8 days postoperatively. The results showed that all groups showed a significant increase in the PET, the moment when comparing pre-injury, with time after the induction of sciatica (3rd day PO). When comparing the time pre-sciatica with the 4th postoperative day, there was a significant difference only for G3. And to make the comparison with the 8th PO, only G1 had a significant difference. By comparing the values obtained on the 3rd postoperative day, with 4 and 8 days PO, decreased significantly for both G2 and G3. Conclude that the mattress produced pain relief, and when the electromagnetic field was active, the restoration of the initial values of PET occurred more quickly.
Keywords: sciatic neuropathy; magnetic field therapy; pain